Muscle transcriptome analysis reveals genes and metabolic pathways related to mineral concentration in Bos indices - Afonso, Juliana; Coutinho, Luiz Lehmann; Tizioto, Polyana Cristine; Silva Diniz, Wellison Jarles da; Lima, Andressa Oliveira de; Pereira Rocha, Marina Ibelli; Buss, Carlos Eduardo; Nascimento Andrade, Bruno Gabriel; Piaya, Otavio; Silva, Juliana Virginio da; Lins, Laura Albuquerque [UNESP]; Gromboni, Caio Fernando; et al. (Nature Publishing Group, 2019)
Mineral content affects the biological processes underlying beef quality. Muscle mineral concentration depends not only on intake-outtake balance and muscle type, but also on age, environment, breed, and genetic factors. To unveil the genetic factors involved in muscle mineral concentration, we applied a pairwise differential gene expression analysis in groups of Nelore steers genetically divergent for nine different mineral concentrations. Here, based on significant expression differences between contrasting groups, we presented candidate genes for the genetic regulation of mineral concentration in muscle. Functional enrichment and protein-protein interaction network analyses were carried out to search for gene regulatory processes concerning each mineral. The core genetic regulation for all minerals studied, except Zn, seems to rest on interactions between components of the extracellular matrix. Regulation of adipogenesis-related pathways was also significant in our results. Antagonistic patterns of gene expression for fatty acid metabolism-related genes may explain the Cu and Zn antagonistic effect on fatty acid accumulation. Our results shed light on the role of these minerals on cell function.